2021
DOI: 10.51253/pafmj.v71i3.6075
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression of P16 in Low Grade Urothelial Carcinoma

Abstract: Objective: To determine the frequency of Immunohistochemical expression of P16 in low grade urothelial carcinoma patients. Study Design: Cross sectional study. Place and Duration of Study: Department of Histopathology, Armed Forces Institute of Pathology, Rawalpindi, from May 2018 to Jul 2019. Methodology: A total of 120 formalin-fixed and paraffin embedded blocks from patients having low grade urothelial carcinomawere included in the study and were stainedimmunohistochemically with P16 antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Urothelial carcinoma of the urinary bladder is one of the most common malignancies in the world, and the prevalence varies across different countries and may differ between the regions of the same country [ 18 , 19 ]. A higher prevalence of urothelial carcinoma of the urinary bladder has been documented in Egypt [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urothelial carcinoma of the urinary bladder is one of the most common malignancies in the world, and the prevalence varies across different countries and may differ between the regions of the same country [ 18 , 19 ]. A higher prevalence of urothelial carcinoma of the urinary bladder has been documented in Egypt [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found a correlation between p16 protein expression and the histological grade of papillary urothelial carcinoma, in addition to a correlation between p16 expression and the muscle invasion of papillary urothelial carcinoma. Previous studies stated that identification of p16 protein expression directly correlates with the tumor behavior and tumor stage where the low-grade tumors and the NMIBCs showed a high expression rate of p16 protein which may help in the process of selecting patients for an early aggressive therapy [ 13 , 18 ]. However, its prognostic significance and the diagnostic utility according to the staining intensity are still unclear, and the studies showed quite different results.…”
Section: Discussionmentioning
confidence: 99%